DECENTRALIZATION AND GOVERNANCE: EVALUATING POLICY EFFECTIVENESS IN FEDERAL STRUCTURES - Shakeel Ahmad Ahanger; Zahoor Ahmad Ahanger; Javid Ahmad Kumar; Nadeem Mohi Ud Din (CV. RADJA PUBLIKA, 2025)
Decentralization, the process of transferring authority and decision-making power from central governments to regional or local governments, plays a critical role in shaping governance in federal systems. This paper explores the relationship between decentralization and governance effectiveness, focusing on how decentralization impacts policy outcomes in federal structures. Through theoretical analysis and case studies from countries such as the United States, India, and Brazil, the paper evaluates the potential benefits and challenges associated with decentralized governance. The study examines how decentralization can improve policy effectiveness by better aligning decisions with local needs, but also highlights issues such as resource disparities, administrative capacity, and coordination challenges. The paper concludes with recommendations on how decentralization can be designed and implemented to enhance policy outcomes, improve governance efficiency, and achieve a more balanced and equitable distribution of public services.